Who influences higher education decision-making in Taiwan? An analysis of internal stakeholders. Issue 10 (2nd October 2020) - Chan, Sheng-Ju; Chou, Chuing
ABSTRACT: In the past two decades, Taiwan has gone through a series of drastic higher education transformations in response to the multi-faceted demands from globalization and domestic social change. Among the driving forces, new public management and neoliberal ideology have reshaped the nature and culture of higher education in Taiwan. The current study focuses on the broader internal stakeholders' relationships to higher education policy as they systematically engage with governance through decision-making. We empirically explore who the main actors are that make decisions at the ministerial level. The study identifies six key groups with different characteristics and traits. Acting as coalitions, these groups frequently influence policy formulation. Moreover, their influential paths – identified as elite approach, professional engagement, and political networking – jointly steer higher education decision-making. These triangular paths serve as a valuable conceptual framework to understand the complicated influential paths from internal stakeholders who have affected Taiwan's higher education policy.